Evaluating the impact of the Belt and Road Initiative for Textile and Clothing companies in Asia - Man Hin Eve Chan; Chi Kuen Danny Hob; Tsz Leung Yipc; Jenny Cheunga; Angappa Gunasekarand (AIBPM Publisher, 2019)
The global identity of the Textile and Clothing (T&C) industry, particularly in T&C manufacturing, can be viewed as no longer being dominated by countries such as China, but shared with developing countries in the ASEAN region as T&C manufacturing moves across borders. The movement of T&C manufacturing from China to ASEAN countries along the Belt and Road (B&R) provides challenges, but also opportunities at both the macro and micro levels. The purpose of this paper is to explore the opportunities that can enhance the mutual supportiveness of trade, and the challenges for progress among B&R countries for T&C trade. The study asks the following questions: what are the challenges and opportunities faced by T&C companies establishing or relocating production to B&R countries, and what tangible actions have already been taken? In-depth interviews were carried out with ten industry professionals from Hong Kong based companies and government institutions involved with T&C trade in B&R counties in Asia. The findings of this study reveals economic development and infrastructure provide opportunities for mutual supportiveness of T&C trade, whilst social factors were identified as the key challenges for T&C manufacturing in ASEAN countries.